2017
DOI: 10.3389/fpls.2017.01998
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of OsEMF2b Caused Semi-sterility Due to Anther and Pollen Development Defects in Rice

Abstract: Anther and pollen development are crucial processes of plant male reproduction. Although a number of genes involved in these processes have been identified, the regulatory networks of pollen and anther development are still unclear. EMBRYONIC FLOWER 2b (OsEMF2b) is important for rice development. Its biological function in floral organ, flowering time and meristem determinacy have been well-studied, but its role, if only, on male reproduction is still unknown, because null mutants of OsEMF2b barely have anther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The vegetative growth of osemf2a-1 and osemf2a-2 was not significantly affected, but the heading date was somewhat delayed in the mutants ( Figure 1 B). Notably, we did not observe floral defects or sterility in osemf2a ( Figure 1 C) as in osemf2b ( Deng et al., 2017 ).
Figure 1 Phenotype of the osemf2a mutants.
…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The vegetative growth of osemf2a-1 and osemf2a-2 was not significantly affected, but the heading date was somewhat delayed in the mutants ( Figure 1 B). Notably, we did not observe floral defects or sterility in osemf2a ( Figure 1 C) as in osemf2b ( Deng et al., 2017 ).
Figure 1 Phenotype of the osemf2a mutants.
…”
Section: Resultsmentioning
confidence: 53%
“…The two Su(z)12-group PRC2 members of rice are OsEMF2a and OsEMF2b ( Luo et al., 2009 ), which likely evolved from an ancient duplication event before the origin of the family Poaceae ( Supplemental Figure 1 A). Previous studies reported that the osemf2b mutant displayed abnormal floral organs, reduced pollen fertility, and decreased dormancy ( Xie et al., 2015 ; Chen et al., 2017 ; Deng et al., 2017 ; Zhong et al., 2018 ). However, we did not identify floral development and fertility issues in osemf2a ( Figure 1 C and 1I).…”
Section: Discussionmentioning
confidence: 99%
“…H3.3 variants correlate with gene expression in Arabidopsis , while H3.1 variants are incorporated during the S-phase of the cell cycle (Borg and Berger, 2015), and references therein). In rice, EMF2 function is essential for pollen development, and it is thought to interact with a rice MSI1 homolog, PTC1 (Deng et al, 2017). Genes encoding homologs of a number of these PRC2 components were also expressed in cowpea pollen development and may have comparable roles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some genes that cause male sterility in rice may affect more than the male gametogenesis, as they may have other mutant related defects. For example, the mutant osemf2bā€4 exhibited a reduced grain number and seed set and the phenotype was shorter than the wild type (Deng et al, ); the mutant osppr676 displayed retarded growth and partial sterility in the pollen grains (Liu et al, ) and this renders these genes unsuitable for hybrid breeding. In this study, we successfully replicated the maleā€sterile phenotype of Oswbc11 mutant in rice using CRISPR/Cas9.…”
Section: Discussionmentioning
confidence: 99%